2021
DOI: 10.1002/aesr.202100045
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Solid Electrocatalysts on Achieving Highly Energy‐Efficient Lithium–Oxygen Batteries

Abstract: Nonaqueous lithium–oxygen (Li–O2) batteries are regarded as a promising electrochemical energy storage technology because of largely defeating commercial Li‐ion batteries on theoretical energy density. However, due to the electrically insulating property of Li2O2, a typical discharge product in Li–O2 batteries, high overpotential is inevitable upon charge. Nonetheless, catalysts could regulate the electrochemical formation pathways of Li2O2, and its morphology is closely bound with the energy required to disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…To tackle the sluggish ORR kinetics, many researchers have focused on the design of solid electrocatalysts. [ 27 ] However, the hunting for electrocatalysts for Li‐O 2 batteries primarily rely on the trial‐and‐error approaches because of an incomplete understanding of the ORR mechanisms in Li‐O 2 batteries so far. Galloway et al.…”
Section: O2 Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…To tackle the sluggish ORR kinetics, many researchers have focused on the design of solid electrocatalysts. [ 27 ] However, the hunting for electrocatalysts for Li‐O 2 batteries primarily rely on the trial‐and‐error approaches because of an incomplete understanding of the ORR mechanisms in Li‐O 2 batteries so far. Galloway et al.…”
Section: O2 Electrochemistrymentioning
confidence: 99%
“…To tackle the sluggish ORR kinetics, many researchers have focused on the design of solid electrocatalysts. [27] However, the hunting for electrocatalysts for Li-O 2 batteries primarily rely on the trial-and-error approaches because of an incomplete understanding of the ORR mechanisms in Li-O 2 batteries so far. Galloway et al [28] reported a study of catalysts screening for Li-O 2 batteries, in which the ORR on distinct electrode materials including Au, Pt, Pd, and GC was examined using the shell-isolated nanoparticles for enhanced Raman spectroscopy (SHINERS).…”
Section: Discharge Pathwaysmentioning
confidence: 99%
“…Growing concerns over the depletion of fossil fuels and damage to the environment call for clean energy storage technologies like rechargeable batteries. , Li-ion batteries (LIBs) have been the dominant power option in the past 30 years but are restricted by their low energy density (<300 Wh/kg) related to their intercalation chemistry. Moving from intercalation chemistry to conversion chemistry, lithium–air batteries (LABs), also called lithium–oxygen batteries (LOBs) in the lab stage with pure O 2 as the reactant, have gained much attention owing to their high theoretical energy density (∼3500 Wh/kg), making them promising alternatives to conventional LIBs. However, currently, several critical issues associated with the Li anode, the electrolyte, and especially the air cathode of LOBs have been puzzling. As a result of the multi-electron-transfer reactions and the undesirable contact of insulating discharge products deposited on the cathode surface, the kinetics of the electro-oxidation of discharge products are sluggish, leading to large charge overpotentials. The high potential as well as reactive oxygen intermediates (ROIs) formed during the charge process would incur severe side reactions and further cause poor cyclability and low energy efficiency of the system. , …”
Section: Introductionmentioning
confidence: 99%